NINJ1 and MMP9: potential biomarkers for intracranial atherosclerosis plaque vulnerability - Wei, Xiao-lian; Da, Xin; Zhang, Yu-ge; Li, Zi-ang; Liu, Bing-jie; Yan, Rui-fang; Zhong, Hua; Yuan, Bin (Frontiers in Neurology, 2025)
Background and objectiveTo utilize high-resolution vessel wall imaging (HR-VWI) to identify the characteristic features of culprit plaques in intracranial atherosclerotic stenosis (ICAS) vessels and evaluate the predictive value of serum nerve injury-induced protein 1 (NINJ1) and matrix metalloproteinase 9 (MMP9) for the vulnerability of intracranial atherosclerotic plaques.MethodsThis study included symptomatic intracranial atherosclerotic stenosis (sICAS) patients who underwent high-resolution vessel wall imaging (HR-VWI) and healthy individuals. Patients were divided into non-enhancement/enhancement, moderate/severe stenosis, and positive/negative remodeling groups. Multivariate logistic regression and receiver operating characteristic (ROC) curve analyses were used to evaluate the predictive value of NINJ1 and MMP9 for plaque enhancement, severe stenosis, and positive remodeling.ResultsNINJ1 and MMP9 levels were higher in the plaque enhancement group compared to the non-enhancement group (107.04 vs. 93.49, p = 0.001; 245.35 vs. 227.16, p = 0.002) and were independent risk factors for plaque enhancement (OR: 1.036, p = 0.003; OR: 1.022, p = 0.008). The area under the curve (AUC) for predicting plaque enhancement by NINJ1 and MMP9 were 0.676 and 0.667, respectively, and the combined AUC was 0.740. In the severe stenosis group, NINJ1 and MMP9 levels were also higher than in the moderate stenosis group (106.28 vs. 94.54, p = 0.006; 243.88 vs. 229.38, p = 0.014), with both being independent risk factors (OR: 1.027, p = 0.012; OR: 1.017, p = 0.027). The AUC for predicting severe stenosis by NINJ1 and MMP9 were 0.652 and 0.646, respectively, and the combined AUC was 0.686. For the positive remodeling group, NINJ1 and MMP9 levels were significantly elevated (108.73 vs. 97.27, p = 0.007; 248.36 vs. 230.42, p = 0.002), and both were independent risk factors (OR: 1.026, p = 0.015; OR: 1.023, p = 0.004). The AUC for predicting positive remodeling by NINJ1 and MMP9 were 0.642 and 0.672, respectively, and the combined AUC was 0.722.ConclusionNINJ1 and MMP9 can serve as independent predictors factors for intracranial atherosclerotic plaque enhancement, severe stenosis, and positive remodeling. NINJ1 and MMP9 have the potential to be serum biomarkers for the vulnerability of intracranial atherosclerotic plaques.